Estimativa de evapotranspiração em bacias hidrográficas, estudo de caso: bacia do rio Santa Joana - Rabello, Livia Luchi (2023)
Evapotranspiration (ET) is a significant process in assessing the water balance, making its estimation highly relevant for water resources management. Estimating evapotranspiration in river basins is a challenging process for a considerable portion of Brazilian hydrographic regions, especially due to the spatiotemporal fragility of hydrometeorological data and uncertainties in representing physical characteristics. Therefore, the objective of this study was to evaluate evapotranspiration estimation using the Soil and Water Assessment Tool (SWAT) model in a small basin in Espírito Santo: the Santa Joana River basin. The SWAT model incorporates three methods, used in this study, for evapotranspiration calculation: Penman-Monteith, PriestleyTaylor, and Hargreaves. In the model calibration, coefficients for the p-factor, r-factor, Nash-Sutcliffe (NS), coefficient of determination (R²), and percent bias (PBIAS) were obtained. The results indicated that the Priestley-Taylor method demonstrated the best performance in simulating flow and evaluating ET in the studied basin, while the Priestley-Taylor and Hargreaves methods did not achieve satisfactory performance. Regarding simulated flows, the model showed more favorable results in simulating minimum flows and less favorable results in simulating maximum flows. This study demonstrated the potential of calibrated hydrological models for estimating evapotranspiration in river basins.